National workshop on the drought action plan for Zambia - Jeya Raj, Renuka; Alahacoon, Niranga; Amarnath, Giriraj; Moyo, C.; Tsegai, D. (International Water Management Institute, 2024)
Zambia, like many regions in southern Africa, has been severely impacted by the 2024 El Niño event. This climate pattern, characterized by warmer-than-average sea surface temperatures in the Pacific Ocean, has triggered prolonged droughts and heatwaves across the country. The agricultural sector, a cornerstone of Zambia's economy and a vital source of livelihood, has been particularly hard-hit by these climatic shocks.